2019
DOI: 10.1088/1538-3873/ab247a
|View full text |Cite
|
Sign up to set email alerts
|

An Optical and X-Ray Study of the Contact Binary, BH Cassiopeiae

Abstract: We present the revised and high-quality CCD time series observations in 2017 and 2018 of the W UMa-type contact binary BHCas. The combination of our new determinations of minimum times and those collected from the literatures reveal a long-term period increase with a rate of dP/dt=+3.27×10 −7 day yr −1 , which can be accounted for by angular momentum transfer as the less-massive component loses its mass to the more massive one. One cyclical oscillation (A′=0.00300 day and P′=20.09 yr) superimposed on … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 88 publications
0
7
0
Order By: Relevance
“…Although the X-ray emission mechanism remains puzzling, the stellar dynamo magnetic activity generated by rapid rotation and envelope convection is usually in consideration (Gondoin 2004a). The studies of BH Cas (Liu et al 2019) and 2MASS J11201034−2201340 (Hu et al 2016) indicate that the X-ray light curves do not show any obvious occultation or modulation as optical light curves would. The X-ray spectra of the former can be described by thermal models, while those of the latter can be both fitted by a thermal or a power-law model.…”
Section: Introductionmentioning
confidence: 99%
“…Although the X-ray emission mechanism remains puzzling, the stellar dynamo magnetic activity generated by rapid rotation and envelope convection is usually in consideration (Gondoin 2004a). The studies of BH Cas (Liu et al 2019) and 2MASS J11201034−2201340 (Hu et al 2016) indicate that the X-ray light curves do not show any obvious occultation or modulation as optical light curves would. The X-ray spectra of the former can be described by thermal models, while those of the latter can be both fitted by a thermal or a power-law model.…”
Section: Introductionmentioning
confidence: 99%
“…Based on present studies, it can be concluded that during the X-ray observations by XMM-Newton, RW Dor and other contact binaries (VW Cep;Gondoin 2004a, 44 Boo;Gondoin 2004b, and BH Cas;Liu et al 2019) were in a quiescent state for some duration. The exact reason for coronal X-ray emission in a quiescent state is debatable in terms of the distribution of magnetic field structures but the presence of loops cannot be ruled out.…”
Section: Loop Size Emitting the Quiescent X-ray Emission In Rw Dormentioning
confidence: 61%
“…Such an orbital period of the third body was observed in VW Cep of about 31 yr (Kaszás et al 1998), which has very similar properties except for the mass ratio. Another source, BH Cas, which exhibits similar properties to RW Dor and VW Cep also has a third body with P 3 = 20.09 yr (Liu et al 2019). For RW Dor, the mass of the third body was noted to be M 3 = 0.175 M e for i = 90°.…”
Section: Non-conservative Mass Loss In Rw Dormentioning
confidence: 95%
See 1 more Smart Citation
“…In contrast, the coronae in TX Cnc have uniformly distributed X-ray emitting regions with both components being equally active and having the same brightness per surface area. Two other contact binaries, BH Cas (Liu et al 2019) and 2MASS J11201034-2201340 (Hu et al 2016) were serendipitously detected in unrelated X-ray observations. For both objects no eclipses or significant variability were found, which may, however, be due to the low signal-to-noise ratio of the X-ray light curves.…”
Section: Introductionmentioning
confidence: 97%